Pengaruh Edukasi Kesehatan Mental Terhadap Perilaku Pencegahan Cyberbullying Pada Remaja Di Kelas X Smk Dewi Laut Bitung - Saida A. Kasim; Helly Katuuk; Sri Wahyuni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Cyberbullying is carried out intentionally and occurs repeatedly in the form of spreading the victim's disgrace or secrets. The efforts made to prevent cyberbullying behavior can be done by providing education about the importance of maintaining mental health. The purpose of this study was to determine whether there was an affect of mental health education on cyberbullying prevention behavior in class X of SMK Dewi Laut Bitung. The research was conducted using the Quash-Experimental method, with one group pre and post test design. The sample taken based on the number of subject as many as 17 using purposive sampling. Data collection using SAP and questionnaire sheets. Furthermore, the data collected processed using SPSS computer programs version 16.0 for analysis of the Paired T-test test with a meaning level (α) of 0.05. The results of research using the Paired T Test found that the value of ρ Value was smaller than the significant value of (0.000<0.05) the results of this study showed that Ha was accepted then H0 was rejected. The conclusion of this study is mental health education on cyberbullying prevention behavior in adolescents in class X of SMK Dewi Laut Bitung was accepted . The advice of the results of this study adolescents can avoid cyberbullying behavior.